AN EXPERIENCE WITH FREE SCAPULAR FLAP FOR RECONSTRUCTION OF LOWER EXTREMITY DEFECTS AT AGA KHAN UNIVERSITY HOSPITAL KARACHI - Hashmi, Pervaiz Mehmood (Journal of Ayub Medical College Abbottabad, 2004)
Back ground: Reconstruction of large composite tissue defects with exposed vital structures and weight bearing surfaces are extremely difficult for reconstructive surgeons. Coverage of such difficult defects can be achieved with free tissue transfer provided microsurgical expertise is available. This study was carried out to determine the outcome of free scapular flaps performed for lower extremity defects. Methods: Clinical records of the patients were reviewed and important variables included demographic data, etiology of soft tissue defects, site and size of defect, complications and percentage of wound coverage by flap. Patient satisfaction and objective assessment of flap coverage and motion of involved joints was made. Results: There were 13 male patients with mean age of 30.46 years. The causes of tissue defects were road traffic accident in 8 cases, industrial accidents in 2 and 3 cases had bomb blast, gunshot and gas gangrene one in each case respectively. Nine scapular flaps were performed to reconstruct the defects around the foot, ankle and lower leg; two flaps for amputation stumps and two flaps for defects around the knee and popliteal fossa. Post flap surgery, 3 cases had vascular compromise which required urgent exploration of anastomosis. Two cases were revived and one flap did not survive. With respect to cosmetic appearance, coverage of required defect, performance of activities of daily living and functional range of motion of involved joints, 6 cases were graded excellent and 7 cases were good. Conclusion: In our cases of lower extremities defects, scapular flap helped to salvage the limb. In conclusion scapular flap is a versatile flap which can be used for lower extremity defects. Key Words: Scapular Flap, lower extremity defects, circumflex scapular artery and vein,